Pengaruh Peran Ibu Dengan Keberhasilan Toilet Training Pada Anak Usia Toddler Di Play Group Tarbiyatush Shibiyan Mojoanyar Mojokerto - Risfan , Batuatas; Tri Peni (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2012)
Most of the mothers still use diapers on their children when they can make a rash around his bottom. The purpose of this study was to determine the effect of the role of mothers with successful toilet training for children ages toddler in Play Group Tarbiyatush Shibiyan Mojoanyar Mojokerto.This type of research used Crossectional design. The indenpendent variable in this study is the role of parents and dependen variable is the success of toilet training. Population in this study were all mothers with children ages toddler in Play Group Tarbiyatush Shibiyan Mojoanyar Mojokerto, and 34 people selected as samples using the purposive sampling technique. Data analyzed using chi square test. The results obtained most of the respondents expressed support in the successful toilet training as many as 14 respondents (56%) and most of the respondents succeeded in potty training children as many as 17 respondents (68%). Chi square test results obtained sig count (ρ) = 0.004 <0.05 so that H0 is rejected, which means there is the influence of the role of mothers with successful toilet training for children ages toddler in Play Group Tarbiyatush Shibiyan Mojoanyar Mojokerto. The necessary patience and attention to a psychic so that toddler can successfully make toilet training. Health workers must provide health education to parents with young children about science-related health of children with toilet training so that parents can find out and provide a supporting role in her toddler.